Two new species of the genus Mallinella Strand, 1906 (Araneae: Zodariidae) from China - Zhang, Feng; Zhang, Bao-Shi; Jia, Xiao-Mei (Zootaxa, 2012)
Two new species of the spider genus Mallinella are reported from China: M. zhui sp. nov. (♂) and M. tianlin sp. nov. (♂).